Gross Anatomy of Humerus of Mudhol Hound Dog - P, Mutturaj. R.; S, Ganga Naik.; P, Sri Sai Anusha.; T, Lakshmishree. K.; M, Dhoolappa. (Indian Journal of Veterinary Anatomy, 2023)
The gross morphological features of humerus of six Mudhol hound dogs were studied.The humerus was very long , slightly twisted, cylindrical with four surfaces. At proximal extremity the lateral tuberosity was prominent, having concavo- convexity surfaces placed above the level of head of the humerus. Several foramina were present between head and lateral tuberosity of humerus. The bicipital groove was undivided. A circular roughened area was present on the caudolateral aspect of lateral tuberosity gives attachment for the infraspinatus muscle. Deltoid tuberosity was prominent and ridge like. Radial fossa and olecranon fossa communicated by means of supratrochlear foramen. Medial epicondyle was prominent, larger than lateral epicondyle. The average mean length of humerus was 22.83±0.02 cm. The average mean breadth at proximal extremity of humerus was 13.54±0.04 cm. The average mean breadth at distal extremity of humerus was 11.82±0.02 cm. The proximal extremity ofhumerus was larger than distal extremity.